Moderating Effect of Family Support on the Mediated Relation Between Negative Life Events and Antisocial Behavior Tendencies via Self-Esteem Among Chinese Adolescents - Gao, Feifei; Yao, Yuan; Yao, Chengwen; Xiong, Yan; Ma, Honglin; Liu, Hongbo (Frontiers in Psychology, 2020)
Adolescents are particularly prone to antisocial behavior. The promoting effect of negative life events on antisocial behavior has been well-documented. However, the internal influence mechanisms between negative life events and antisocial behavior tendencies in adolescents are still unknown. The aim of this study was to explore the mediation effect of self-esteem and the moderated mediation effect of family support between negative life events and antisocial behavior tendencies in 8,958 adolescents who were selected from three Chinese provinces. Robust maximum likelihood estimator of a structural equation model was applied to test the mediation model and the moderated mediation model. The results revealed that negative life events had a positive effect on antisocial behavior tendencies in adolescents, with a direct effect of 0.082 (95%CI: 0.052, 0.111) and an indirect effect via self-esteem of 0.168 (95%CI: 0.146, 0.191). Negative life events had a 67.20% effect on antisocial behavior tendencies, where self-esteem showed mediation. The indirect effect was 2.049-fold greater than the direct effect. Furthermore, the effect of latent interaction of subjective family support and negative life events on self-esteem was negatively significant (β = -0.018, p = 0.032, 95%CI: -0.035, -0.002). The indirect effect of negative life events was greater where subjective family support was below 1 standard deviation of the mean (conditional indirect effect = 0.227, 95%CI = 0.200, 0.255) than where it was above 1 standard deviation of the mean (conditional indirect effect = 0.203, 95%CI = 0.177, 0.229). The moderated mediation effect index was -0.012, p = 0.033. Moderated mediation showed that the mediated path was less evident in the students who had greater subjective support from family. The results of the current study demonstrated the important role that self-esteem and subjective family support played in minimizing the adverse effect of negative life events on antisocial behavior development of adolescents. These findings have important implications for preventing antisocial behavior in adolescents by developing interventions aimed at enhancing their self-esteem and providing support-skill training to parents aimed at improving subjective family support of adolescents.